Dynamic reading techinique to motivate students to learn english as a second language at the tenth grades in Daniel O. Crespo High School - González Núñez, Dwight Elan Mauricio (David, Panamá : UDELAS, 2015)
This study wukk orivude you a guide abouta what is happening in our educational enviroment now. Thus, this investigation will include a lot of important data that will offer meaningful information about why students are not getting the necessary English knowledge to be able to acquire English as a second language in high school.
TABLE OF CONTENTS TABLE INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM 1.1. Antecedents 1.2. Statement of the problem 1.3. Objectives 1.3.1. General objective 1.3.2. Specific Objective 1.4. Justification 1.5. Scope and delimitation CHAPTER II: THEORICAL FRAMEWORK 2.0. What is language 2.0.1. What is language? 2.0.2. What is learning? 2.0.3. Acquisition / learning 2.0.4. Comraing and constrasting first and second language acquisition 2.0.4.1. The acqusition learning hypothesis 2.0.4.2. The critical period hypothesis 2.0.4.3. Fossilization 2.1. What is reading? 2.1.1. Effective reading 2.1.2. Reading skills 2.1.3. Reading fluency 2.1.4. Vocabulary development through reading 2.2. What is literacy? 2.3. The importance of vocabulary learning 2.3.1. Vocabulary is the key to communication 2.3.2. Good skills by learning vocabulary 2.4. Types of vocabulary 2.4.1. Receptive 2.4.2. Productive 2.4.3. Vocabulary mastery 2.5. Teaching vocabulary 2.5.1. Teaching vocabulary with realia 2.5.2. Teaching vocabulary using drawings 2.5.3. Using ilustrations and pictures to teach vocabulary 2.5.4. Comparison and contrast 2.5.5. Enumeration 2.5.6. Guessing from context 2.6. Strategies when learning vocabulary 2.7. The importance of vocabulary when reading in english 2.8. The reading process 2.8.1. Skim and preview 2.8.2. Read quickly and do not stop 2.8.3. The reading process y otros capítulos más CHAPTER III: METHODOLOGY 3.1. Type of research 3.2. Source of information 3.3. Material source 3.2.2. Subject 3.2.2.1. Population 3.2.2.2. Sample 3.2.2.3. Kind of sample (Questionnaire) 3.3. Variables 3.3.1. Conceptual definition 3.3.2. Instrumental definition 3.3.3. Operational definition 3.4. Instrumental description 3.5. Information treatment CHAPTER IV: Analysis of the results obtained in the ivestigation Graphic #1 Graphic #2 Graphic #3 Graphic #4 Graphic #5 Graphic #6 Graphic #7 Graphic #8 Graphic #9 Graphic #10 CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHIY ANNEXES
Incluye Tabla de contenido
Documento presentado para optar al título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TECHNIQUES; ENGLISH -- TESIS DE LICENCIATURA -- SECOND LANGUAGE; ESCUELA DE PEDAGOGÍA DOCENCIA DE INGLES; DANIEL O. CRESPO HIGH SCHOOL